Etiopatogenia de la endometriosis - Celis López, Alfredo (2026)
Endometriosis is a complex chronic disease characterized by a chronic estrogen-dependent inflammatory process that mainly affects pelvic tissues, including the ovaries, and affects a significant number of women worldwide.